(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Pesticide are used extensively in agriculture to enhance food production by eradicating unwanted insects. Pesticide can cause harm to human, animals, or the environment. The aim of this study to evaluate the biochemical changes in human of different occupational groups exposed to pesticide. Material and methods: The cross sectional comparative study was conducted in the department of biochemistry Chattogram Medical College, from January 2012 to December 2012. Total 100 subjects who fulfilled the enrollment criteria were included in this study. Among them 60, who were exposed to pesticides were included in group A or case or test subject and 40 who were not exposed to pesticides were included in group B or control. The occupational groups exposed to pesticide were randomly selected on the basis of their active involvement at least 5 years in preparation, storage and spraying of the pesticides. Results : The present study showed that serum Cholinesterase(ChE) was significantly lower in cases than that of control with p= <0.001. In this study observed that 45% cases decreased ChE level. Regarding serum SGPT , it is significantly increase in cases than that of control (45.05 ± 16.08 vs 31.85± 4.25 U/L, p= <0.001). It is also observed that nearly 45% cases increased SGPT and SGOT level in cases( Group A). Conclusion: It was found that there is a significant decrease in serum cholinesterase in insecticide spraying workers while serum SGPT and SGOT were increased in exposed group. It is thus concluded from the findings of the study that clinicians and epidemiologists should advice occupationally exposure group to periodic screening test for serum ChE, SGPT, SGOT to detect the effect of pesticides before adverse health effect to occur. JCMCTA 2018 ; 29 (2) : 41-46